Low prevalence of helminth infection in Ugandan children hospitalized with severe malaria - Drew Capone; Nuzrath Jahan; Ruth Namazzi; Robert O. Opoka; Chandy C. John (PLoS ONE, 2025)
Co-infection by intestinal helminths and Plasmodium spp. may be common in endemic communities. In 2003, Uganda instituted a national deworming program, with anti-helminth medication provided twice annually to children 6 months to 5 years of age, but few follow-up studies have been conducted. Several studies have identified a relationship between helminth infection, Plasmodium spp. infection and malaria severity. However, the relationship is not well defined, and results are inconclusive. We analyzed 177 stool samples from a cohort of children with severe malaria enrolled in two hospitals in Uganda from 2014–2017. All children were 6 months to 48 months of age and had a clinical presentation of and laboratory confirmation for severe malaria. We also analyzed 25 stool samples from community children who were negative for malaria via rapid diagnostic test and were enrolled from the same household or neighborhood and matched by age, sex, and time of enrollment. We investigated if intestinal helminth infection modified risk of severe malaria. We extracted nucleic acids from stool and tested them for six helminth species (Anyclostoma duodenale, Ascaris lumbricoides, Necator americanus, Strongyloides stercolaris, Trichuris trichiura, Shistosoma mansoni) using highly sensitive quantitative PCR. We found a low prevalence of infection by ≥1 intestinal helminth species in children with severe malaria (5.1%, n = 9/177) and community control children (4.0%, n = 1/25). Helminth infection did not increase or decrease the risk of severe malaria in this cohort (aRR = 1.0, 95% Confidence Interval = 0.82, 1.3, p = 0.78). In these areas of Uganda, the national deworming campaign has been highly successful, as stool-based helminth infection was rare even when using sensitive methods of detection and helminths were not associated with severe malaria in this study.